1998
DOI: 10.1063/1.121715
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of the size effect in thin ferroelectric films

Abstract: Ferroelectricity in sol-gel derived Ba 0.8 Sr 0.2 TiO 3 thin films using a highly diluted precursor solution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 8 publications
0
33
0
3
Order By: Relevance
“…(ii) A thin parasitic interfacial layer, which has a small capacitance component, acts electrically in series with the rest of the film and reduces the effective dielectric constant and remanent polarisation in the system [225,226,228,238,241,243]. The physics of the ferroelectriceelectrode boundary (such as intrinsic surface polarisation effects [237,243], depolarisation fields due to incomplete screening by the electrodes [240], intrinsic suppression of polarisation at the electrode [239]) or some heteroepitaxial induced effects (like oxygen depletion zones [244], local diffusion of electrode material onto the ferroelectric [236], lattice mismatched induced ion vacancy formation [227], chemically different surface phase or surface contamination [220,223,237]) have indeed been proposed for the peak broadening effect. (iii) In the dead layer model, recently proposed by Sinnamon et al for films with columnar microstructure, dead layers at the grain boundaries rather than at the ferroelectrice electrode interface were considered [234,235].…”
Section: Thickness Dependencementioning
confidence: 99%
“…(ii) A thin parasitic interfacial layer, which has a small capacitance component, acts electrically in series with the rest of the film and reduces the effective dielectric constant and remanent polarisation in the system [225,226,228,238,241,243]. The physics of the ferroelectriceelectrode boundary (such as intrinsic surface polarisation effects [237,243], depolarisation fields due to incomplete screening by the electrodes [240], intrinsic suppression of polarisation at the electrode [239]) or some heteroepitaxial induced effects (like oxygen depletion zones [244], local diffusion of electrode material onto the ferroelectric [236], lattice mismatched induced ion vacancy formation [227], chemically different surface phase or surface contamination [220,223,237]) have indeed been proposed for the peak broadening effect. (iii) In the dead layer model, recently proposed by Sinnamon et al for films with columnar microstructure, dead layers at the grain boundaries rather than at the ferroelectrice electrode interface were considered [234,235].…”
Section: Thickness Dependencementioning
confidence: 99%
“…9 and 12, we use values of 100 nm for ␣ 1 and ␣ 2 , and L, the thickness of the film. With a correlation coefficient D * of the order of ϳ10 −9 ͑SI units͒, 9,19,20 the value of the flexoelectric coefficient is ͑␥ − ͒ = 0.1ϫ 10 −9 m 3 C −1 . We note that parameters for the penetration depth of the strain ͑␣ 1 and ␣ 2 ͒ are very important for the polarization profiles in ferroelectric thin films, through which properties of the thin film may then be controlled experimentally.…”
Section: ͑5͒mentioning
confidence: 99%
“…[7][8][9][10] However, no definitive origin for the proposed dielectric "dead-layer" has yet been discovered. Some researchers have suggested that it is associated with fundamental interface physics, [10][11][12][13][14][15] but there are a great number of other hypotheses which are capable of generating series capacitance behavior: strain gradients; 16,17 physical layers of low permittivity either adjacent to the electrodes in the capacitor, 18,19 or at grain boundaries in the ferroelectric; 20 parasitic capacitance associated with the finite charge screening lengths in nonideal electrodes; [21][22][23][24] even subtleties in device asymmetry. 25 Such a variety of possible explanations for permittivity suppression makes for interesting and active debate, but it equally leads to a great deal of confusion and uncertainty, and does not clearly define how detrimental effects on permittivity might be avoided.…”
mentioning
confidence: 99%